Mammary type adenocarcinoma of the vulva: a rare case report - Kashyap, Arnika A.; Modi, Kanika B.; Chaturvedi, Harit K.; Agrawal, Komal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A primary vulvar mammary type of adenocarcinoma is an exceptionally rare malignancy that is thought to arise from mammary-like vulvar glands. Its low incidence is partly responsible for the lack of guidelines for patient management. We present a case of a 74-year-old woman who presented with a palpable mass in her vulvar region and was submitted to an excisional biopsy, which was diagnosed as mammary-type adenocarcinoma. The patient then underwent a partial vulvectomy with unilateral inguinal sentinel lymph node biopsy followed by adjuvant hormonal therapy. This case report highlights the challenges in diagnosing and managing this rare entity and emphasizes the importance of a multidisciplinary approach to providing optimal care for patients with a mammary type of adenocarcinoma of the vulva.